Characteristics of In Situ Stress and Reservoir Pressure in Deep Coal Seams and Their Influences on Reservoir Depletion: A Field Case Study. (20th February 2023) - Li, Rui; Lu, Yiyu; Xia, Binwei; Chen, Wenwen; Sun, Hansen
Abstract : The production of coalbed methane resources is greatly dependent on the reservoir depletion process. To improve the depressurization efficiency of deep coalbed methane (DCBM) reservoirs, the fluid production characteristics and implications of in situ stress and reservoir pressure for reservoir depletion in the eastern margin of the Ordos Basin are analyzed. The results indicate that the duration of the single-phase water production stage is overall long, with the gas declining stage occurring too early. The daily gas production volume of DCBM wells is only a few hundred m 3 . For DCBM reservoirs, it is considered that in situ stress, initial reservoir pressure, and critical desorption pressure significantly affect the fluid production and depressurization process. A high in situ stress in deep coal seams is likely to damage the flow conductivity of fracture systems due to the increase in effective stress during reservoir depletion. Based on the in situ stress characteristics of deep coal seams and their implications for reservoir depletion, we propose that the depressurization of DCBM reservoirs during gas production can be promoted via a new method of stress release. Slots or cavities created in coal seams by high-pressure hydraulic jet can provide space for stress release. This novel depressurization method could help improve the gas production efficiency of DCBM reservoirs.